THE ROLE OF EDUCATION AND TRAINING IN YOUTH DEVELOPMENT (American Journal of Interdisciplinary Research and Development, 2023)
In this article, education - upbringing and national education in our country since ancient times that spirituality has always been inextricably linked and their universality developed together with values, national education spiritual foundations, spiritual and moral education and its main component, spiritual and moral education and its requirements are known in the society formation of moral feelings corresponding to social and moral requirements in accordance with the mind, emotions and behavior of students and education it is stated that the system has been formed.